1989
DOI: 10.1113/jphysiol.1989.sp017558
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐derived relaxing factor inhibits the formation of inositol trisphosphate by rabbit aorta.

Abstract: SUMMARY1. The effects of endothelium-derived relaxing factor (EDRF), sodium nitroprusside, 8-bromo-cyclic GMP and atrial natriuretic factor (ANF) on inositol trisphosphate (jP3) levels were studied in isolated rabbit aortic preparations stimulated with noradrenaline.2. In endothelium-containing preparations, acetylcholine, which stimulated EDRF release, inhibited noradrenaline-stimulated 1P3 formation. The EDRF inhibitor haemoglobin reversed this effect.3. In endothelium-denuded preparations, sodium nitropruss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…Even if NO was added 20 s after AII (after the peak increase in [Ca 2ϩ ] i caused by the agonist), the ionomycin-induced release was 26Ϯ9% greater than in the absence of NO (564Ϯ63, PϽ0.04; Figure 8C), consistent with an NO-induced augmentation of the refilling of Ca 2ϩ stores. Inhibition of the peak increase in [Ca 2ϩ ] i caused by AII could be achieved by either inhibition of Ca 2ϩ release from the stores 7,19 or by accelerated sequestration of Ca 2ϩ into the stores. The role of uptake by SERCA was determined by releasing Ca 2ϩ from the stores with AII in the absence or presence of TG.…”
Section: Camentioning
confidence: 99%
“…Even if NO was added 20 s after AII (after the peak increase in [Ca 2ϩ ] i caused by the agonist), the ionomycin-induced release was 26Ϯ9% greater than in the absence of NO (564Ϯ63, PϽ0.04; Figure 8C), consistent with an NO-induced augmentation of the refilling of Ca 2ϩ stores. Inhibition of the peak increase in [Ca 2ϩ ] i caused by AII could be achieved by either inhibition of Ca 2ϩ release from the stores 7,19 or by accelerated sequestration of Ca 2ϩ into the stores. The role of uptake by SERCA was determined by releasing Ca 2ϩ from the stores with AII in the absence or presence of TG.…”
Section: Camentioning
confidence: 99%
“…In maximally contracted arteries the dominant mechanism of relaxation appears to be uncoupling of stress development from myosin phosphorylation, rather than alterations in [Ca2"]i or the [Ca2+]i sensitivity of myosin phosphorylation, whereas in submaximally constricted tissues, and therefore presumably under physiological conditions, relaxation is also mediated by decreases in [Ca2+]i (Morgan & Morgan, 1984;McDaniel, Chen, Singer, Murphy & Rembold, 1992). The mechanisms participating in this decrease in [Ca2"] include: (1) stimulation of a plasmalemmal Ca2"-extrusion ATPase (Popescu, Panoiu, Hinescu & Nutu, 1985) and Na'-Ca2" exchange (Furukawa, Ohshima, Tawada-Iwata & Shigekawa, 1991), (2) depression of agonist-stimulated phosphoinositide turnover through reduced G protein activation and uncoupling of activated G protein to phospholipase C (Rapoport, 1986;Lang & Lewis, 1989;Hirata, Kohse, Chang, Ikebe & Murad, 1990), (3) increased sequestration of cytosolic Ca2+ in sarcoplasmic reticulum secondary to phosphorylation of phospholamban and activation of the Ca2+-ATPase pump (Twort & van Breemen, 1988;Lincoln & Cornwell, 1991), (4) attenuated Ca2" influx through both receptor-and voltage-operated Ca2" channels which are inhibited by cGMP-dependent protein kinase (Collins, Griffith, Henderson & Lewis, 1986;Blayney, Gapper & Newby, 1991;Ishikawa, Hume & Keef, 1993), and (5) membrane hyperpolarization, which closes voltage-operated Ca2" channels (Nelson, Patlak, Worley & Standen, 1990;Tare, Parkington, Coleman, Neild & Dusting, 1990) and reduces IP3 formation and its subsequent mobilization of Ca2" from internal stores (Itoh, Seki, Suzuki, Ito, Kajikuri & Kuriyama, 1992).…”
Section: Smooth Muscle Mechanisms Activated By Edrfmentioning
confidence: 99%
“…No discernible changes in cytosolic PKC activity were noted under the same conditions. We have previously shown that cyclic GMP causes inhibition of 1P3 production in both vascular smooth muscle (Lang & Lewis, 1989) and cultured endothelial cells of the pig (Lang & Lewis, 1991). An inhibition of DAG production from PIP2 could account for the effect of cyclic GMP on the early rise in endothelin-l-induced particulate PKC, since cyclic GMP is thought to exert its effect at the site of the G protein coupling receptor to phospholipase C .…”
Section: Discussionmentioning
confidence: 98%
“…It is known that cyclic GMP inhibits phosphatidylinositol (PI) hydrolysis in vascular smooth muscle (Rapoport, 1986) and platelets (Takai et al, 1981). More recently it has been shown that in both vascular smooth muscle and endothelium this effect of cyclic GMP leads to inhibition of agonist-induced inositol 1,4,5-trisphosphate (1P3) production (Lang & Lewis, 1989;. However, this effect of cyclic GMP on IP3 production does not adequately explain the mechanism of inhibition of vascular smooth muscle tone during the tonic phase of contraction, which involves PKC activation.…”
Section: Introductionmentioning
confidence: 99%